Persepsi Masyarakat Muslim terhadap Produk Kosmetik Halal (Studi Kasus Mahasiswa FEBI UIN K.H. Abdurrahman Wahid Pekalongan) - Dwi Mukti Rosalita; Farsya Ashila Yumna; Nunung Yuliani; Amelia pramestika; Sabila Rizqiyani (Journal Economic Excellence Ibnu Sina, 2023)
Cosmetic products are beauty products such as skincare or make up which are made from a mixture of chemicals and are generally used to beautify a person. Halal lifestyle has now become a trend in society causing the demand for halal products, for example cosmetic products to increase rapidly. In Indonesia, halal labeling or halal certification is carried out by the MUI after various checks have been carried out. The research objective is to see how the Muslim community views cosmetic products that meet halal requirements. The research method used is field research where the main focus of this research is to find out public perceptions of halal cosmetic products that occur in the field. The data used are primary and secondary data. Primary data obtained from interviews. While secondary data is obtained from literature sources that are relevant to the research discussed, both from books, journals and other sources that support this research. The results of the study show that there is a positive response from the community regarding halal cosmetic products. The perception that is most often conveyed is that cosmetic products that have received halal status can already be ascertained that their substance content is safe and their benefits can be guaranteed because they have received an MUI halal certificate and passed the BPOM test.